2011
DOI: 10.1037/a0021818
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic drumming across the lifespan reveals a zone of proximal development in children.

Abstract: Many social interactions require the synchronization-be it automatically or intentionally-of one's own behavior with that of others. Using a dyadic drumming paradigm, the authors delineate lifespan differences in interpersonal action synchronization (IAS). Younger children, older children, younger adults, and older adults in same-and mixed-age dyads were instructed to drum in synchrony with their interaction partner at a constant, self-chosen tempo. Adult-only dyads showed the highest and childrenonly the lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 97 publications
0
28
0
Order By: Relevance
“…Comparisons between these three conditions probably contribute to potential interactions between tempo and the number of participants. The duration of each trial was set at 200 s, which was considered sufficient for the long-term ITI fluctuation observed in a previous study23. Soon after one participant completed a trial, the other participant began a solo trial, following the same procedure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparisons between these three conditions probably contribute to potential interactions between tempo and the number of participants. The duration of each trial was set at 200 s, which was considered sufficient for the long-term ITI fluctuation observed in a previous study23. Soon after one participant completed a trial, the other participant began a solo trial, following the same procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Further, the number of taps in a single trial was limited to 32 (no more than 20 s), which was too short to allow assessment of ITI drift over longer timescales, such as those of full musical pieces that continue for several minutes. In other studies involving paired SC tapping or similar tasks, task durations were limited to several tens of seconds17181920212223. These durations are insufficient to judge whether ITI drift in paired SC tasks is similar to that in solo SC tasks, in which ITI time series display long periods of fluctuation (for as long as 50–100 s15).…”
mentioning
confidence: 99%
“…For example, children's unilateral or bilateral drumming performance can be facilitated by having an adult drum with the child (Kirschner and Tomasello, 2009; Kleinspehn-Ammerlahn et al, 2011). We hypothesize that if deficiencies in the interpersonal coordination of rhythmic incidental movements occur in ASD, it may provide a window into understanding some of the minimal underlying motoric dynamic deficiencies that might restrain a child from being solidly grounded in a social world.…”
Section: Autism and Social Disconnection In Interpersonal Rockingmentioning
confidence: 99%
“…Nowicki also found that visual contact had no effect. Kleinspehn (2008;Kleinspehn-Ammerlahn et al, 2011) showed that individual synchronization skill, as assessed by tapping with a metronome, predicted dyadic synchronization accuracy in various mixed-age groups (5-78 years). In addition, young children performed better when paired with an older partner.…”
mentioning
confidence: 99%